Gas exchange and adaptive structural characteristics of coffee plants grown in different levels of radiation - Baliza, Danielle Pereira; Cunha, Rodrigo Luz; Castro, Evaristo Mauro; Barbosa, João Paulo Rodrigues Alves Delfino; Pires, Marinês Ferreira; Gomes, Rodrigo Abreu (Coffee Science - ISSN 1984-3909, 2012)
Differences in the radiation levels can cause modifications in the structural and functional characteristics of the leaves,which can respond differentially by anatomical, morphological and photosynthetic modifications. The objective of the present workwas to verify the possible modifications in the foliar anatomy and photosynthetic characteristic of coffee plants in the formation phasesubmitted to different radiation levels. After the planting of the coffee plants in the field, they were submitted to five radiation levels (fullsun and under plastic screens providing 35, 50, 65 and 90% shade). The treatments were appraised as to the gas exchange and foliaranatomy ten months after the installation of the assay in field. The amount of incident radiation influences the internal structure of thecoffee plants leaves and their respective functions. The 90% shade level is not recommended for the cultivation of the coffee plant,because it reduces the photosynthetic rate, presenting lower mesophyll and palisade parenchyma thickness. The 35% shade level ismore recommended for coffee plant cultivation in a shaded environment. At that level, improvement of the internal structure of theleaves occurs that can favor interesting physiological characteristics to optimize the development of that culture.